BIOCHEMICAL AND PHYSIOLOGICAL PREDICTORS OF STRESS-INDUCED HYPERTENSION AMONG MEDICAL STUDENTS: A CROSS-SECTIONAL STUDY : http://doi.org/10.46536/jpumhs/2024/14.02.522 - Saima Naz Shaikh1, Arsalan Ahmed Uqaili2, Tazeen Shah3, Abeer Memon4, Farheen Shaikh5, Saira Dars6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
Background: Medical students are exposed to significant stress, potentially leading to hypertension. This study aims to identify biochemical and physiological predictors of stress-induced hypertension among medical students. Methods: A cross-sectional study involving 300 medical students was conducted. Participants were categorized into high-stress and low-stress groups based on Perceived Stress Scale (PSS) scores. Physiological measurements, including blood pressure (BP), heart rate variability (HRV), and pulse rate, were recorded. Biochemical markers such as salivary cortisol, urinary catecholamines, and oxidative stress markers (MDA and antioxidant enzymes) were analysed. Correlations between stress levels and these markers were assessed. Results: The high-stress group showed significantly higher systolic BP (130.1 mmHg vs. 117.8 mmHg, p < 0.001) and diastolic BP (83.4 mmHg vs. 75.2 mmHg, p < 0.001), lower HRV (35.4 ms vs. 50.2 ms, p < 0.001), and elevated pulse rate (82.7 bpm vs. 72.1 bpm, p < 0.001). They also had elevated cortisol levels, higher catecholamine excretion, and increased oxidative stress. Significant correlations were found between PSS scores and systolic BP (r = 0.61, p < 0.001), cortisol levels (r = 0.58, p < 0.001), and oxidative stress markers (r = 0.55, p < 0.001). Conclusion: High stress in medical students is associated with increased BP, elevated stress hormones, and greater oxidative stress, underscoring the need for stress management interventions.